Literary Heritage of the First Ideologist of the Moscow Kingdom. Review of: Daniel, Metropolitan of Moscow. Works, ed. by L.I. Zhurova. Moscow, Indrik Publ., 2020, 848 p - Dmitry M. Bulanin (Studia Litterarum)
This review analyzes the first academic publication of the works written by Metropolitan Daniel (1522–1539). He was the head of Russian Church in the years when the Moscow principality was being transformed into the Moscow kingdom, which claimed its proper place in the providential history. The hierarch is well known to literary critics as the initiator of wide-scale book enterprises that proclaimed the symbolic dignity of Moscow in its new function of the “Third Rome.” Daniel’s own writings, concentrated in four large units, had little chance to attract attention because they neglected the problems relevant for his time. An exemplary publication of Daniel’s writings prepared by L.I. Zhurova as well as the text history of his writings makes it possible to revise the traditional estimation of this part in Daniel’s books heritage. The reviewer draws attention to the structural innovations made by Daniel who enriched Russian literature with new genres and new forms. As it turns out, the allegedly dull works of the Metropolitan are closely related to his work as an ideologist of the Russian state.